Intestinal transplantation in The Netherlands: first experience and future perspectives. - Dijkstra, G; Rings, E; Bijleveld, C; Van Dullemen, H; Hofker, H; Porte, R; Ploeg, R (2006)
Intestinal transplantation for intestinal failure is no longer an experimental procedure, but an accepted treatment for patients who fail total parenteral nutrition (TPN) therapy. Early referral for evaluation for small bowel transplantation has to be considered in patients with permanent intestinal failure who have occlusion of more than two major veins, frequent line-related septic episodes, impairment of liver function or an unacceptable quality of life. With the increased experience in post-transplant patient care and newer forms of induction (thymoglobulin, IL-2 receptor antagonists) and maintenance (tacrolimus) therapies the 1-year graft survival has increased to 65% for isolated and to 59% for liver/small bowel transplantation, and is further improving. Rejection, bacterial, fungal and viral (CMV, EBV) infection, post-transplant lymphoproliferative disease (PTLD) and graft versus host disease (GvHD) are the most common complications after intestinal transplantation. Although most of the long-term survivors are TPN-independent and have a good quality of life, the risk of the procedure and long-term adverse effects of immunosuppressive medication limits small bowel, or liver/small bowel transplantation only to patients with severe complications of TPN therapy.